The risk of overestimating cost savings from hospital-at-home schemes: A literature review. (September 2020) - Goossens, Lucas M.A.; Vemer, Pepijn; Rutten-van Mölken, Maureen P.M.H.
Abstract: Background: The concept of hospital-at-home means that home treatment is provided to patients who would otherwise have been treated in the hospital. This may lead to lower costs, but estimates of savings may be overstated if inpatient hospital costs are priced incorrectly. Objective: The objective of this study was to evaluate the quality of cost analyses of hospital-at-home studies for acute conditions published from 1996 through 2019 and to present an overview of evidence. Design: Literature review Data Sources: The PubMed and NHS EED databases were searched. Review Methods: The overall quality of studies was evaluated based on Quality of Health Economic Studies (QHES) score, design, sample size, alignment of cost calculation with study perspective, time horizon, use of tariffs or real resource use and clarity of calculations. Furthermore, we systematically assessed whether cost savings were likely to be overestimated, based on criteria about the costing of inpatient hospital days, informal care costs and bias. Results: We identified 48 studies. The average QHES score was 60 out of a maximum of 100 points. Almost all studies violated one or more criteria for the risk of overestimation of cost savings. The most frequent problems were the use of average unit prices per inpatient day (not taking into account the decreasing intensity of care) and biased designs. Most studies found cost differences in favour of hospital-at-home; the range varied from savings of €8773 to a cost increase of €2316 per patient. Conclusion: Overall quality of studies was not good, with some exceptions. Many cost savings were probably overestimated.